1996
DOI: 10.1093/brain/119.3.889
|View full text |Cite
|
Sign up to set email alerts
|

An event-related potential study of recognition memory with and without retrieval of source

Abstract: Event-related potentials (ERPs) were recorded during the test phase of a recognition memory task in two experiments. In both experiments subjects made initial old/new judgements to visually presented words, and for words judged old, indicated in which of two voices (male/female) the words had been heard at study. In the second experiment only subjects had the option to signal that they were uncertain about the status of a test word. Two positive-going ERP effects differentiated the ERPs evoked by correctly rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
343
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 534 publications
(402 citation statements)
references
References 40 publications
54
343
5
Order By: Relevance
“…An item's source can be defined as any of a number of contextual features that accompany the occurrence of an event, including perceptual (e.g., speaker's gender [74]; picture's color [14] and temporal (e.g., sequential list in which the item occurred [67]) characteristics. Memory for contextual features, especially spatiotemporal aspects, appears to be particular vulnerable to increasing age [60], compared to simple recognition of the item as "old" (item memory).…”
Section: Source and Item Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…An item's source can be defined as any of a number of contextual features that accompany the occurrence of an event, including perceptual (e.g., speaker's gender [74]; picture's color [14] and temporal (e.g., sequential list in which the item occurred [67]) characteristics. Memory for contextual features, especially spatiotemporal aspects, appears to be particular vulnerable to increasing age [60], compared to simple recognition of the item as "old" (item memory).…”
Section: Source and Item Memorymentioning
confidence: 99%
“…During more typical source memory paradigms, distinct physical item features identify the two sources (e.g. color [14] or speaker's voice [74]). However, in recency memory paradigms such distinct physical features are not necessarily available as the temporal order of presentation is the critical piece of information that needs to be retrieved.…”
Section: The Role Of the Frontal Lobes In Strategy Usementioning
confidence: 99%
“…Source memory task (Wilding and Rugg, 1996). This task was chosen as an index of episodic memory, that is, awareness of when and where a stimulus was encoded.…”
Section: Cognitive Tasksmentioning
confidence: 99%
“…These results also confirmed that participants correctly 361 attended to the actual emotional content of the scenes throughout the experiment. (Curran 391 and Cleary, 2003;Curran and Doyle, 2011;Sanquist et al, 1980;Wilding and Rugg, 1996;392 Wilding et al, 1995), and provide converging evidence that our short-term memory manipulation 393 was successful. 394…”
Section: Emotion Classification Task 352mentioning
confidence: 75%
“…These results are 555 consistent with previous studies (Curran and Cleary, 2003;Curran and Doyle, 2011;Weymar et 556 al., 2009;Wilding and Rugg, 1996;Wilding et al, 1995), and provide converging evidence that 557 our short-term memory manipulation was successful. However, neither the main effect of 558 emotion nor the emotion x memory interaction were significant (all ps > .05), indicating 559 comparable old/new effects for neutral and emotional scenes.…”
Section: New and Old Scenes Recruit Non-overlapping Brain Network Dumentioning
confidence: 82%